2003
DOI: 10.1021/jm030865y
|View full text |Cite
|
Sign up to set email alerts
|

Optically Active Mexiletine Analogues as Stereoselective Blockers of Voltage-Gated Na+ Channels

Abstract: Optically active mexiletine analogues were synthesized and evaluated in vitro as use-dependent blockers of skeletal muscle sodium channels. The mexiletine analogues were obtained by replacing either the methyl group on the stereogenic center of mexiletine [1-(2,6-dimethylphenoxy)propan-2-amine] with a phenyl group or modifying the phenoxy moiety (by removal of one or both of the methyl groups, or introducing a chlorine atom), or both. The voltage clamp recordings showed that, regardless of the substitution pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 39 publications
(74 reference statements)
1
43
0
Order By: Relevance
“…1), markedly enhanced drug potency. 17 The sum of these findings prompted us to synthesize two new compounds (2 and 3, Fig. 1) in order to better explore the importance of the position of the stereogenic center relative to the terminal amino group of Mex on the homologated alkyl chain of 1.…”
Section: Introductionmentioning
confidence: 99%
“…1), markedly enhanced drug potency. 17 The sum of these findings prompted us to synthesize two new compounds (2 and 3, Fig. 1) in order to better explore the importance of the position of the stereogenic center relative to the terminal amino group of Mex on the homologated alkyl chain of 1.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] In the past years, a series of selective serotonine (5-HT)-reuptake inhibitor (SSRI) antidepressants (e.g. Fluoxetine and Paroxetine) and selective norepinephrine (NE)-reuptake inhibitor antidepressants (e.g.…”
Section: An Efficient Catalyst-free Four-component Synthesis Of Novelmentioning
confidence: 99%
“…4 More recently, several mexiletine analogs have been identified that have greater potency for inhibition of Na + channel currents with a stereochemical preference for (R)-mexiletine analogs. 5 Several approaches to the preparation of mexiletine enantiomers have been reported. Chiral resolution of mexiletine was first reported using a chiral co-crystallization method, 4,6 and later by derivatization of the racemate with a removable chiral auxiliary.…”
Section: Introductionmentioning
confidence: 99%
“…9 Among de novo syntheses, Franchini and colleagues have reported a number of approaches to synthesize enantiomers of mexiletine or its metabolites by stereospecific transformations of chiral precursor molecules. 5,10 In one example, ring-opening of (R)-or (S)-propylene oxide with xylenol provided a chiral alcohol that was subsequently converted to individual enantiomers of mexiletine. 11 Sasikumar and co-workers have applied Jacobsen's hydrolytic kinetic resolution to a racemic epoxide precursor of mexiletine and the resolved chiral epoxide was subsequently converted to (R)-mexiletine.…”
Section: Introductionmentioning
confidence: 99%